Longitudinal physical activity and sedentary behaviour in preschool-aged children with cerebral palsy across all functional levels - Keawutan, P.; Bell, K.; Oftedal, S.; Ware, R.; Stevenson, R.; Davies, P.; Boyd, Roslyn (Wiley-Blackwell Publishing Ltd., 2017)
Aim: To investigate longitudinal changes of habitual physical activity (HPA) and sedentary time in children with cerebral palsy (CP) aged 1 year 6 months to 5 years across all functional abilities. Method: At study entry, 95 children (62 males, 33 females) were classified using the Gross Motor Function Classification System (GMFCS) at levels I (50), II (9), III (16), IV (6), and V (14). Physical activity was recorded on a total of 159 occasions at four possible time points: 1 year 6 months to 2 years; 2 years 6 months to 3 years; 4 years; and 5 years using ActiGraph for 3 days. Mixed-effects regression models were used for analyses. Results: Participants classified at GMFCS levels I and II had stable HPA as they aged. HPA significantly decreased at 5 years in children classified at GMFCS levels III to V. Sedentary time significantly increased at 4 years and 5 years in all participants. Annual HPA significantly reduced in children classified at GMFCS levels III to V (-123 counts/min, 95% confidence interval [CI] -206 to -40) while annual sedentary time significantly increased in all participants (GMFCS levels I-II: 2.4%, 95% CI 0.7-4.1; GMFCS levels III-V: 6.9%, 95% CI 4.6-9.2). Interpretation: Children with CP at all GMFCS levels should be encouraged to be physically active from early childhood as HPA levels start to decline from 4 years. Breaks in sedentary time are required for all children with CP from the age of 3 years.